The specifics of English-language borrowings in the French youth argot (on the material of a literary text) - Kudriavtseva, Natalia A. (Вестник Томского государственного университета. Филология)
The language of modern French youth is a phenomenon that arouses the interest of researchers who classify algorithms for decoding non-conventional lexemes. Young French people create their own subculture, trying at the same time to prevent other generations from penetrating this special world. For this purpose, young people resort to the use of various linguistic tools. The most reliable way of codification is the transformation of the word form. One of the simplest means of achieving this modification is the use of English lexical units that go into the French language in their original meaning or take on completely new interpretations. The relevance of studying the youth vocabulary is due to the rapid adaptation of the representatives of this reference group to the changing conditions of the modern world. As a result, there is a significant replenishment of the vocabulary of young people, which requires a study of the linguistic features of the designated social category. The analysis of the argotic repertoire allows us to understand the worldview of modern French youth, to assess the goals of using English borrowings in speech. Non-conventional lexemes used by young people are part of various youth argot dictionaries and are also recorded in texts reflecting musical culture and in literary works by modern French writers. The major priority of our research is to show how young people use argotic words formed on the basis of English borrowings. The received lexemes were characterised on the basis of argotographic publications. At the stage of collecting and studying the English-language argotic elements used by French youth in the analysed books, the following methods were applied: the descriptive-analytical and comparative methods, the corpus analysis and the method of symptomatic statistics. The article analyses English borrowings incorporated into the novels Kiffe kiffe demain by Faïza Guène, Bloody Black Pearl by Laurence Chevallier, Silent boy by Gaël Aymon and La chambre des merveilles by Julien Sandrel. The peculiarities of assimilation and semantic adaptation of English argotisms are considered. Examples of the extracted lexemes are given in the contextual environment; the frequency of their use is determined. As a result of the study, a conclusion was made about the important role played by non-conventional English vocabulary in the transmission of characteristic linguistic features of youth speech.